2013
DOI: 10.1136/jclinpath-2013-201544
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of icteric index as approach to detect abnormal total bilirubin values

Abstract: We read with great interest the article by Salinas et al 1 suggesting the use of the icteric index (II) as a front-line test for the preliminary identification of blood samples with abnormal total bilirubin (TB) concentrations. Following the authors' suggestion, we were encouraged to experimentally confirm their findings in our own hospital setting. Particularly, in our laboratory we use platforms (Cobas c 501 and Integra 800) and reagents of the same vendor (Roche Diagnostics) used by Salinas et al, and we th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
3
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 3 publications
1
3
0
Order By: Relevance
“…Regarding the second objective of this study, we set I-index cut-off with the highest specificity and lowest false positive results, finding similar results than others studies with I-index ≥ 34.2 µmol/L (16)(17)(18). Hyperbilirubinemia diagnosis could be important in these cases to know the subjacent aetiology, such as Gilbert syndrome, hepatocellular damage, biliary obstruction, haemolytic anaemia, or others (12).…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…Regarding the second objective of this study, we set I-index cut-off with the highest specificity and lowest false positive results, finding similar results than others studies with I-index ≥ 34.2 µmol/L (16)(17)(18). Hyperbilirubinemia diagnosis could be important in these cases to know the subjacent aetiology, such as Gilbert syndrome, hepatocellular damage, biliary obstruction, haemolytic anaemia, or others (12).…”
Section: Discussionsupporting
confidence: 63%
“…To our knowledge, this is the first study that evaluates I-index on Alinity c. It is well known that the icteric index is correlated to total bilirubin but we checked it in our platform (16)(17)(18)(19). Several studies have been published with the objective of reducing number of TBil tests with two main platforms, Roche and Abbott (16)(17)(18)(19)(20)(21). An interesting study of HIL index in these two platforms showed an unacceptable comparability between them (15).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An additional interesting use of the determination of II, first proposed by Salinas et al ,2 is its use as front-line test for the identification of blood samples with abnormal total bilirubin (TB) concentrations. The application of an optimal cut-off for II that reliably identifies abnormal TB concentrations allowed the accurate ‘zero-cost’ detection of samples with normal TB concentrations (ie, ≤0.012 g/L or ≤20.5 µmol/L), avoiding direct measurements in ~40% of bilirubin orders 3. In our laboratory, the use of II for the screening of hyperbilirubinaemic samples was validated in 2015 using the Abbott Architect c16000 analytical system and, since June 2016, serum and plasma samples with a request of TB determination and an II ≤0.8 are automatically reported as having a TB concentration ≤0.012 g/L (≤20.5 µmol/L), without any further measurement 4.…”
mentioning
confidence: 99%